2003
DOI: 10.1042/bj20021829
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of the human phosphodiesterase 7A1 promoter

Abstract: In this paper, the human phosphodiesterase 7A1 (hPDE7A1) promoter region was identified and functionally characterized. Transient transfection experiments indicated that a 2.9 kb fragment of the hPDE7A1 5 -flanking region, to position − 2907, has strong promoter activity in Jurkat T-cells. Deletion analysis showed that the proximal region, up to position − 988, contains major cis-regulatory elements of the hPDE7A1 promoter. This minimal promoter region contains a regulatory CpG island which is essential for pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…115 In Jurkat T cells, overexpression of CRE binding protein (CREB) increases the promoter activity. In human CD4…”
Section: Phosphodiesterasementioning
confidence: 99%
“…115 In Jurkat T cells, overexpression of CRE binding protein (CREB) increases the promoter activity. In human CD4…”
Section: Phosphodiesterasementioning
confidence: 99%
“…On the other hand, PDE7A2, which is generated by 5Ј-splicing and differs from PDE7A1 at its N terminus (Bloom and Beavo, 1996;Han et al, 1997), was never detected at the protein level, despite unequivocal identification of its mRNA (Smith et al, 2003). The distribution of PDE7A3 is largely unknown, but it has been found in human T-lymphocytes (Glavas et al, 2001) and may also be present in many PDE7A1-expressing cells as both transcripts are probably regulated by the same promoter (Torras-Llort and Azorin, 2003). In contrast, PDE7B is abundant in the brain, liver, heart, thyroid glands, and skeletal muscles, but it is not found in leukocytes (Gardner et al, 2000).…”
mentioning
confidence: 99%
“…Studies by Glavas and coworkers (45) identified this splice variant in human CD4 ϩ T lymphocytes after costimulation with anti-CD3/CD28 antibodies, but its distribution in other cells is unknown. Given that PDE7A3 and PDE7A1 are probably regulated by the same promoter (43), it is possible that the expression pattern of the two transcripts is similar.…”
Section: Pde7mentioning
confidence: 98%
“…Two genes (PDE7A and PDE7B) have been identified in the mouse, rat, and human that encode PDE7 isoenzymes (36,(39)(40)(41)(42). The coding region of HSPDE7A spans 124 kb and contains 14 exons (43). Screening of murine and human skeletal muscle DNA libraries has identified three splice variants (PDE7A1, PDE7A2, and PDE7A3) derived from the same gene.…”
Section: Pde7mentioning
confidence: 98%